Digital Curation and Costs: Approaches and Perceptions - Corujo, Luís (2017)
The production of large volumes of scientific information, considering its cost, requires approaches that ensure its maintenance, reuse and recovery. These concerns prompted the emergence of digital curation. We intend to discuss the relevant thinking concerning the costs of digital curation. This means addressing the definition of the concept and the issue of costs, based on the studies related to cost models. A literature review was conducted using B-On and RCAAP as research sources, exploring the perceptions of the authors regarding the digital curation and its costs. The views expressed were organized around a scheme based on the Digital Curation Centre (DCC) lifecycle and the reference model Open Archival Information System (OAIS). It is proposed a systematization of digital curation issues bridging the DCC life cycle view of the digital object curation to the OAIS reference model approach, using a cross view seized by cost models and plan/data management policies.